PERAN PERPUSTAKAAN DALAM MEMBANGUN CITRA PERPUSTAKAAN DI ERA TEKNOLOGI INFORMASI - Sri Anawati (Jurnal Pustaka Ilmiah, 2016)
Library as a source of information is expected to become a life-long learning forpemustakanya. Currently, the library has adopted a variety of information technology development in order to provide various services to the pemustakanya. Therefore, the image of the library should be built in order to thrive in this era of globalization. A good library can be seen and measured on their success in meeting the needs of the user and can serve with the capabilities to society user. By building a positive image of the library, where the library will bring and develop the image of the institution, both within and outside of their parent institutions. In meeting the needs of improvingthe image of the college library, then the library must have a strategy three (3) pillars of the main image. First, build an image library (image building), both improve the image of the librarian (librarian image), and the three libraries based on information and communication technology or Information and Communication Technology (ICT based). With developed a library based on information and communication technology. or Information and Communication Technology (ICT), both in the management information system of the library and digital library, then the library can provide services to the maximum, comfort, convenience to library users, convenience to the librarian staffs, good in service and processing as well in implementing strategies for, library development. This of course will improve the image of the library in providing convenience facilities library services provided to the user.